World Health Organization infant and young child feeding indicators and their associations with child anthropometry: a synthesis of recent findings. Issue 1 (15th August 2013) - Jones, Andrew D.; Ickes, Scott B.; Smith, Laura E.; Mbuya, Mduduzi N.N.; Chasekwa, Bernard; Heidkamp, Rebecca A.; Menon, Purnima; Zongrone, Amanda A.; Stoltzfus, Rebecca J.
Abstract As the World Health Organization (WHO) infant and young child feeding (IYCF) indicators are increasingly adopted, a comparison of country‐specific analyses of the indicators' associations with child growth is needed to examine the consistency of these relationships across contexts and to assess the strengths and potential limitations of the indicators. This study aims to determine cross‐country patterns of associations of each of these indicators with child stunting, wasting, height‐for‐age z‐score (HAZ) and weight‐for‐height z‐score (WHZ). Eight studies using recent Demographic and Health Surveys data from a total of nine countries in sub‐Saharan Africa (nine), Asia (three) and the Caribbean (one) were identified. The WHO indicators showed mixed associations with child anthropometric indicators across countries. Breastfeeding indicators demonstrated negative associations with HAZ, while indicators of diet diversity and overall diet quality were positively associated with HAZ in Bangladesh, Ethiopia, India and Zambia (P < 0.05). These same complementary feeding indicators did not show consistent relationships with child stunting. Exclusive breastfeeding under 6 months of age was associated with greater WHZ in Bangladesh and Zambia (P < 0.05), although CF indicators did not show strong associations with WHZ or wasting. The lack of sensitivity and specificity of many of the IYCF indicators may contribute to the inconsistent associations observed. The WHO indicators are clearly valuable tools for broadly assessing the quality of child diets and for monitoring population trends in IYCF practices over time. However, additional measures of dietary quality and quantity may be necessary to understand how specific IYCF behaviours relate to child growth faltering.